Integrative Analysis of the Transcriptome and Metabolome Reveals Genes Involved in Phenylpropanoid and Flavonoid Biosynthesis in the Trapa bispinosa Roxb. - Yin, Dong-Jie; Ye, Shi-Jie; Sun, Xiao-Yan; Chen, Qin-Yi; Min, Ting; Wang, Hong-Xun; Wang, Li-Mei (Frontiers in Plant Science, 2022)
Background Trapa bispinosa Roxb. is grown worldwide as an important aquatic cash crop. Current research on Trapa bispinosa primarily focuses on the separation and identification of active ingredients, as well as the inhibitory effect on tumors; however, research on the molecular mechanism of secondary metabolite accumulation is rather limited. Consequently, an integrative analysis of transcriptome and metabolome is required to identify the key metabolic pathways, and key genes, and to explain the molecular mechanism of Trapa bispinosa. Results The biosynthesis pathways of phenolics in Trapa bispinosa were examined through transcriptome and metabolome analyses. Transcriptome analysis yielded 42.76 million clean reads representing 81,417 unigenes with an average length of 1,752 bp. KEGG pathway analysis revealed that 1,623 unigenes, including 88 candidate unigenes related to phenolics biosynthesis, were up-regulated in Trapa bispinosa shell (FR) when compared to leaves (LF), root (RT), and stem (ST). The FR vs. LF group had the highest number of specific genes involved in phenylpropanoid, flavonoid, flavone, and flavonol biosynthesis pathways compared to all other comparison groups. In addition, RNA sequencing revealed 18,709 SSRs spanning 14,820 unigenes and 4,387 unigenes encoding transcription factors. Metabolome analysis identified 793 metabolites, including 136 flavonoids and 31 phenylpropane compounds. In the FR group compared to the LF group, there were 202 differentially accumulated metabolites (DAMs). The combined transcriptome and metabolome analyses indicated a significant correlation between 1,050 differentially expressed genes (DEGs) and 62 DAMs. This view proposes a schematic of flavonoid biosynthesis in the FR vs. LF group, providing evidence for the differences in genes and metabolites between FR and LF. Conclusion In this study, through de novo transcriptome assembly and metabolome analysis, several DEGs and DAMs were identified, which were subsequently used to build flavonoid biosynthesis pathways and a correlation network. The findings pave the way for future research into the molecular mechanisms and functional characterization of Trapa bispinosa candidate genes for phenolics biosynthesis.